SYNCHRONY AS A SEGMENT OF DIACHRONY: (Old Church Slavonic Grammar by Emilija Crvenkovska, printed by Blaže Koneski Faculty of Philology,Ss. Cyril and Methodius University in Skopje, 2021, 234 pages) (Journal of Contemporary Philology, 2021)
(Old Church Slavonic Grammar by Emilija Crvenkovska, printed by Blaže Koneski Faculty of Philology,Ss. Cyril and Methodius University in Skopje, 2021, 234 pages)
Keywords: Review